Health social movements and the hybridisation of 'cause regimes': an ethnography of a British childbirth organisation. (3rd July 2016) - Roberts, Celia; Tyler, Imogen; Satchwell, Candice; Armstrong, Jo
Abstract: This article reports on an ethnographic study of the UK's largest health advocacy organisation dedicated to pregnancy, childbirth and parenting, the National Childbirth Trust or NCT. Working from interview data, textual materials and fieldnotes, we articulate three key phases in the NCT's historically shifting relationships to feminism, medicine, the state and neoliberal capitalism. The concept of folded cause regimes is introduced as we examine how these phases represent the hybridisation of the organisation's original cause. We argue that for the NCT the resulting multiplicity of cause regimes poses significant challenges, but also future opportunities. The apparent contradictions between cause regimes offer important insights into contemporary debates in the sociology of health and illness and raises critical questions about the hybrid state of health advocacy today. Focussing on cause allows for a deeper understanding of the intense pressures of diversification, marketisation and the professionalisation of dissent faced by third-sector organisations under current social and economic conditions.